Inoculation of Triatoma Virus (Dicistroviridae: Cripavirus) elicits a non-infective immune response in mice - Querido, Jaison F. B. (2013)
Dicistroviridae is a new family of small, non-enveloped, +ssRNA viruses pathogenic to both beneficial arthropods and insect pests. Little is known about the dicistrovirus replication mechanism or gene function, and any knowledge on these subjects comes mainly from comparisons with mammalian viruses from the Picornaviridae family. Due to its peculiar genome organization and characteristics of the per os viral transmission route, dicistroviruses make good candidates for use as biopesticides. Triatoma virus (TrV) is a pathogen of Triatoma infestans (Hemiptera: Reduviidae), one of the main vectors of the human trypanosomiasis disease called Chagas disease. TrV was postulated as a potential control agent against Chagas? vectors. Although there is no evidence that TrV nor other dicistroviruses replicate in species outside the Insecta class, the innocuousness of these viruses in humans and animals needs to be ascertained.